Pastoral livestock losses and post-drought rehabilitation in subsaharan Africa: Policy options and issues - Toulmin, C. (International Livestock Centre for Africa, 1986)
This paper examines post-drought rehabilitation policies to aid recovery in pastoral livestock production in Africa. It starts by describing the main impact of drought on livestock production and the sequences of this for the national economy. It considers the range of policy options open to governments and development agencies in this area and the problems associated with each one. It then examines the provision of credit to herders to aid in the reconstitution of livestock holdings, and associates the particular issues with the implementation of such projects. The paper focusses on policies which may be carried in the short to medium term to mitigate drought-related losses.